ANALISIS HUBUNGAN BELANJA MODAL DAN BELANJA PEMELIHARAAN PADA ANGGARAN PUSKESMAS TOLANGOHULA - Radjak, Lukfiah Irwan (JSAP : Journal Syariah and Accounting Public, 2023)
This research aims to find out whether capital expenditure and maintenance expenditure have a significant relationship to the budget of the Tolangohula Community Health Center. The research design used is a causal design. The statistical tests used to test the hypothesis that the author proposes are the Pearson Product Moment correlation, correlation significance test, and coefficient of determination. Showed that capital expenditure had a positive and significant relationship with maintenance expenditure in the Tolangohula Health Center budget. The correlation result is 0.554, which means that there is a 55.40% relationship between capital expenditure and maintenance expenditure in the Tolangohula Health Center budget. The result of the coefficient of determination (r2) is 0.307. This value means 30.70% of capital expenditure is an estimate of maintenance expenditure in the Tolangohula Community Health Center budget. The positive coefficient results indicate that the greater the capital expenditure allocated for various facilities and infrastructure at the Tolangohula Health Center, the greater the maintenance expenditure allocated for various health facility maintenance activities.